2021
DOI: 10.1111/1462-2920.15437
|View full text |Cite
|
Sign up to set email alerts
|

Low airborne tenacity and spread of ESBL‐/AmpC‐producing Escherichia coli from fertilized soil by wind erosion

Abstract: ESBL-/AmpC-producing Escherichia coli from organic fertilizers were previously detected on soil surfaces of arable land and might be emitted by wind erosion. To investigate this potential environmental transmission path, we exposed ESBL-/AmpC-positive chicken litter, incorporated in agricultural soils, to different wind velocities in a wind tunnel and took air samples for microbiological analysis. No data exist concerning the airborne tenacity of ESBL-/AmpCproducing E. coli. Therefore, we explored the tenacity… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…Various pathways for the transmission of AMR E. coli from livestock reservoirs to humans are conceivable, including the consumption of contaminated meat products (Overdevest et al, 2011; Randall et al, 2021), direct contact to animals (Dahms et al, 2015; de Been et al, 2014), and environmental routes, for example, in association with aerosols or insect vectors (Friesema et al, 2012). The airborne spread of E. coli is limited by the pathogen's low desiccation tolerance (Siller et al, 2021). The common house fly ( Musca domestica ), however, has been identified as a vector of AMR E. coli and diverse other pathogens (Graczyk et al, 2001; Khamesipour et al, 2018; Onwugamba et al, 2018; Yin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Various pathways for the transmission of AMR E. coli from livestock reservoirs to humans are conceivable, including the consumption of contaminated meat products (Overdevest et al, 2011; Randall et al, 2021), direct contact to animals (Dahms et al, 2015; de Been et al, 2014), and environmental routes, for example, in association with aerosols or insect vectors (Friesema et al, 2012). The airborne spread of E. coli is limited by the pathogen's low desiccation tolerance (Siller et al, 2021). The common house fly ( Musca domestica ), however, has been identified as a vector of AMR E. coli and diverse other pathogens (Graczyk et al, 2001; Khamesipour et al, 2018; Onwugamba et al, 2018; Yin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the disposal of manure or manure-derived products as fertilizer on agricultural land may lead to environmental contamination with C. difficile spores. The survival of C. difficile in fertilized agricultural soil and its release with surface water runoff or dust has as yet not been investigated, in contrast to other manure-derived pathogens, including Escherichia coli, Salmonella enterica, Campylobacter spp., Clostridium perfringens and Enterococcus faecium (Blaustein et al, 2015;Thiel et al, 2020;Siller et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research had also shown that the temperature (Wang et al 2020a) and wind (Siller et al 2021) had an impact on the temporal microbial community and metabolome changes in Baijiu, so we inferred that a low wind speed and a warm, humid climate were concerned with Baijiu fermentation. Utilising meteorological data from four different regions, we dis- The average maximum temperature in Luzhou is not more than 30 °C, and the average minimum temperature is not less than 5 °C, as shown in Figure 4A.…”
Section: Macro Ecological Environment Analysismentioning
confidence: 72%